A Stress Memory Effect in Olivine at Upper Mantle Pressures and Temperatures - T. Ohuchi; Yuji Higo; Noriyoshi Tsujino; Sho Kakizawa; Yusuke Seto; Yoshio Kono; Hirokatsu Yumoto; Takahisa Koyama; Hiroshi Yamazaki; Yasunori Senba; Haruhiko Ohashi; Ichiro Inoue; et al. (Geophysical Research Letters)
Abstract Cyclic deformation experiments on olivine aggregates have been conducted at pressures of 1.9–2.8 GPa and temperatures of 297–1250 K. Measurements of mechanical data combined with acoustic emission (AE) monitoring revealed that activity of AE increased with differential stress and ceased once loading was halted in the anelastic regime. AE output abruptly recommenced when the differential stress exceeded the previous maximum stress during a reloading cycle at temperatures lower than 1150 K (i.e., the stress memory effect). In contrast, a number of AEs radiated even at stresses much less than the previous maximum stress (i.e., breakdown of the memory effect) as a result of a 1‐hr annealing treatment at 1250 K before each reloading cycle. These observations are explained by the accumulation/release of back stress in olivine crystals. Due to sluggish release of back stress in olivine, the stress memory effect could be effective under the pressure‐temperature conditions of subducting slabs.